O valor da expressão
![\frac{ {x}^{2} - 1 }{ {x}^{3} - 1} \frac{ {x}^{2} - 1 }{ {x}^{3} - 1}](https://tex.z-dn.net/?f=+%5Cfrac%7B+%7Bx%7D%5E%7B2%7D+-+1+%7D%7B+%7Bx%7D%5E%7B3%7D+-+1%7D+)
quando x=i (unidade imaginária é:
a) i+1
b)
![\frac{(i + 1)}{2} \frac{(i + 1)}{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B%28i+%2B+1%29%7D%7B2%7D+)
c)
![\frac{ - (i + 1)}{2} \frac{ - (i + 1)}{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B+-+%28i+%2B+1%29%7D%7B2%7D+)
d)-(i-1)
e)
![\frac{(i - 1)}{2} \frac{(i - 1)}{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B%28i+-+1%29%7D%7B2%7D+)
Soluções para a tarefa
Respondido por
3
Perguntas interessantes